Do cage fish farms promote interference in the trophic niche of wild fish in neotropical reservoir? - Kliemann, Bruna Caroline Kotz [UNESP]; Delariva, Rosilene Luciana; de Oliveira Manoel, Letícia [UNESP]; dos Santos Silva, Amanda Pereira [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP]; Ramos, Igor Paiva [UNESP] (Elsevier, 2022)
Cage fish farming in hydroelectric reservoirs has been reported to promote variations in environmental conditions, which directly interfere with the foraging behavior of wild fish. We have hypothesized that the abundance of foods derived from fish farming activities alters the interspecific relationships of wild fish. To test this, we evaluated the diet composition, trophic niche breadth, and trophic niche overlap of the wild fish fauna sampled in two areas (cage farm and control area). Changes in diet composition between areas were observed, resulting in contraction of the trophic niche, and partitioning of food resources in the cage farm area. These results indicate the complexity of the influence of cage fish farms and demonstrate the importance of studies on the wild fish fauna under the influence of these systems. Furthermore, the species evaluated here have economic potential for local fishing, and our results suggest the maintenance of fish stocks in the short term due to the energy supply of the cages.
Keywords: Aquaculture; Feed intake; Feeding; Niche breadth; Niche overlap; Wild ichthyofauna